Mental disorders in the media: A retrospective study of newspaper coverage in the Chilean Press. (November 2022) - Grandón, Pamela; Fernández Vega, Dany; Sánchez Oñate, Alejandro Antonio; Vielma Aguilera, Alexis Vladimir; Villagrán Valenzuela, Loreto; Vidal Gutiérrez, Daisy; Inostroza Rovengno, Carolina; Whitley, Rob
Background: The mass media are relevant in shaping the population's attitudes towards mental disorders. In low- and middle-income countries there is little information about the portrayal of people with mental disorders in the mass media. Aim: The general objective of the study was to assess the tone and content of Chilean newspaper articles about mental disorder from 2000 to 2019. Method: The digital editions of four national circulation Chilean newspapers were intentionally selected. The search engine Google News was used to identify and retrieve the news. To evaluate the news, a standardised codebook was administered. A total of 385 news were evaluated. Results: The results show that a large proportion of the news items has an overall positive/optimistic tone 43.5% and 57.5% does not stigmatise; however, only 18.4% emphasises recovery as part of the content. The highest percentages of news stigmatising in tone and content are observed for bipolar disorder and schizophrenia. Furthermore, the experts are quoted much more frequently than people diagnosed with mental disorders or their families and/or friends. When comparing by years there is a trend towards general decrease in stigmatisation, moving towards a more positive or optimistic view of mental health, Conclusions: In general, low stigmatisation towards mental disorders was found in the news and this was reduced steadily over time. Although there are aspects to improve in some particular areas, suggesting that manifest stigma has diminished, but more subtle forms still remain.